Measurement of the ratio of B+ and B0 meson lifetimes - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (American Physical Society (APS), 2005)
The ratio of the B+ and B0 meson lifetimes was measured using data collected in 2002-2004 by the D0 experiment in RunII of the Fermilab Tevatron Collider. These mesons were reconstructed in B→μ+νD*-X decays, which are dominated by B0 and B→μ+νD̄0X decays, which are dominated by B+. The ratio of lifetimes is measured to be τ+/τ0=1. 080±0.016(stat)±0.014(syst). © 2005 The American Physical Society.